Access to vocational education and training for refugees : insights into Germany, Austria and Switzerland - Busse, Robin [Verfasser]; Bock-Schappelwein, Julia [Verfasser]; Kammermann, Marlise [Verfasser] (My University, 2024)
"Vocational education and training is considered to be crucial for the successful occupational integration of young refugees. Findings from Germany, Austria and Switzerland show that these countries are adopting different routes in order to support the integration of refugees despite commonalities in the structure of their VET systems. The article mainly focuses on the phases of preparation for and access to VET." (authors' abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; S 1.2 Berufsvorbereitung; G 1.3.2.2 Übergänge; I 2.2.1 Westeuropa; 370; Flüchtling; Berufsvorbereitung; Berufsausbildungsvorbereitung; Berufseinmündung; Internationaler Vergleich; Schweiz; Österreich; Bundesrepublik Deutschland